2015
DOI: 10.2147/ijn.s80397
|View full text |Cite
|
Sign up to set email alerts
|

Development and molecular characterization of polymeric micro-nanofibrous scaffold of a defined 3-D niche for in vitro chemosensitivity analysis against acute myeloid leukemia cells

Abstract: Standard in vitro drug testing employs 2-D tissue culture plate systems to test anti-leukemic drugs against cell adhesion-mediated drug-resistant leukemic cells that harbor in 3-D bone marrow microenvironments. This drawback necessitates the fabrication of 3-D scaffolds that have cell adhesion-mediated drug-resistant properties similar to in vivo niches. We therefore aimed at exploiting the known property of polyurethane (PU)/poly- l -lactic acid (PLLA) in forming a micro-nanofibrous str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Hematological malignancy of acute leukemia is highly heterogeneous. At present, there are no standardized chemotherapy regimens for acute lymphoblastic leukemia (ALL) bone marrow microenvironment (1), with specific three dimensional (3D) structure, can support the growth of leukemia cells as well as protect them from chemotherapy drug induced death (24). 3D scaffold needs some properties to better mimic the bone marrow environment, such as adequate pore size, interconnected pores and high surface area, which will facilitate cells penetration and the formation of cellular associations (5).…”
Section: Introductionmentioning
confidence: 99%
“…Hematological malignancy of acute leukemia is highly heterogeneous. At present, there are no standardized chemotherapy regimens for acute lymphoblastic leukemia (ALL) bone marrow microenvironment (1), with specific three dimensional (3D) structure, can support the growth of leukemia cells as well as protect them from chemotherapy drug induced death (24). 3D scaffold needs some properties to better mimic the bone marrow environment, such as adequate pore size, interconnected pores and high surface area, which will facilitate cells penetration and the formation of cellular associations (5).…”
Section: Introductionmentioning
confidence: 99%
“…Nair et al developed a polyurethane (PU)/poly-Llactic acid (PLLA) micro-nanofibrous scaffold by a thermally induced phase separation technique. Acute Myeloid Leukemia (AML) cells cultured in the scaffold showed an increased cell adhesion and drug resistance (65). Phan Lai et al used hybrid 3D chitosan-alginate fibre scaffolds for the in vitro evaluation of tumour−stromal−T cell interactions.…”
Section: Fibrous Scaffolds As In Vitro Cancer Modelsmentioning
confidence: 99%
“…Because many of the elements of xenografts are out of the researcher’s control, three dimensional in vitro models of hematological malignancies have been developed for AML 204, 205 , follicular lymphoma 206, 207 , B cell lymphoma 208, 209 , and multiple myeloma 210–214 . With the modularity of tissue engineering, these 3D models are highly adaptable to be disease specific.…”
Section: Engineered Ex Vivo Models Of Hematological Malignancies Amentioning
confidence: 99%
“…With the modularity of tissue engineering, these 3D models are highly adaptable to be disease specific. While culturing techniques like using the hanging drop method for the formation of aggregates 207, 215 required little engineering for microenvironment development, microenvironment tailoring has been achieved through manipulation of biomaterial stiffness 209 , strength 212 , integrin ligand presentation 208, 209 , inclusion of stromal cell support 204, 213 , and morphology 205 . Even though tailored tissue engineered constructs are over-simplifications of the tumor microenvironment, the presence of these 3D structures in cancer drug trials has been shown to produce different responses when compared to traditional 2D cell culture 204, 206–209, 212 .…”
Section: Engineered Ex Vivo Models Of Hematological Malignancies Amentioning
confidence: 99%